The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/00048674211025714
|View full text |Cite
|
Sign up to set email alerts
|

‘In the night kitchen’: A scoping review on the night eating syndrome

Abstract: Background: First described in 1955, night eating syndrome refers to an abnormal eating behavior clinically defined by the presence of evening hyperphagia (>25% of daily caloric intake) and/or nocturnal awaking with food ingestion occurring ⩾ 2 times per week. Aims: Although the syndrome is frequently comorbid with obesity, metabolic and psychiatric disorders, its etiopathogenesis, diagnosis, assessment and treatment still remain not fully understood. Methods: This review was conducted according to PRISMA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…Research on disordered eating behaviors related to obesity is essential to inform preventative strategies and treatment. Multiple factors appear to in uence the link between NES and BMI, such that some studies have found a direct association while others, including the current study, have not (see [40] for review). Still, symptoms of NES can be expected to (at least) contribute to excess weight.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Research on disordered eating behaviors related to obesity is essential to inform preventative strategies and treatment. Multiple factors appear to in uence the link between NES and BMI, such that some studies have found a direct association while others, including the current study, have not (see [40] for review). Still, symptoms of NES can be expected to (at least) contribute to excess weight.…”
Section: Discussionmentioning
confidence: 69%
“…For example, evening hyperphagia is common among individuals with obesity [41] and nocturnal eating is associated with signi cant weight gain [42]. In addition to other, more severe eating pathology that might be present [23], NES patients are undoubtedly at high risk for developing and maintaining obesogenic behaviors and metabolic syndrome [40]. The multifactorial nature of NES demands several preventative and treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Research on disordered eating behaviors related to obesity is essential to inform preventative strategies and treatment. Multiple factors appear to influence the link between NES and BMI, such that some studies have found a direct association, while others, including the current study, have not (see [ 40 ] for review). Still, symptoms of NES can be expected to (at least) contribute to excess weight.…”
Section: Discussionmentioning
confidence: 78%
“…For example, evening hyperphagia is common among individuals with obesity [ 41 ] and nocturnal eating is associated with significant weight gain [ 42 ]. In addition to other, more severe eating pathology that might be present [ 23 ], NES patients are undoubtedly at high risk for developing and maintaining obesogenic behaviors and metabolic syndrome [ 40 ]. The multifactorial nature of NES demands several preventative and treatment options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation